Methodology proposal for budgeting process on manufacturing and logistics organisation - Serol, Paulo António Gromicho (2022)
Based on an analysis of the most relevant literature on the topic, and on the solutions proposed by academics or the ones other organisations are implementing, different planning models to better understand the budgeting process, the common difficulties encountered, and the solutions proposed by different agents. As such, this study explores the better budgeting and the beyond budgeting models, as well as the tools these models propose, namely, Activity Based Budgeting, Zero-based budgeting, Rolling Budgeting and External Benchmarking. Having worked on the organisation for more than five years as manager and having a deep knowledge of the used budgeting process the focus was on understanding the difficulties on the budgeting process, the existing proved methods, and tools, and see how they fit on the organisation to propose them as solution. Several of the difficulties and problems mentioned on the literature were identified on the organization’s process and following the author’s view on how to overcome them, actions were proposed though the change of behaviours following the method’s principles or by using the tools available on the mentioned methods.